2022
DOI: 10.4018/ijebr.293295
|View full text |Cite
|
Sign up to set email alerts
|

Customer Inclination on Mobile Wallets With Reference to Google-Pay and PayTM in Bengaluru City

Abstract: In this cashless economy era, Information and Communication Technology (ICT) plays a vital role in making payments using various payment modes. The mobile wallet app is an innovative technology for avoiding the usage of physical cash. The mobile wallet records all kinds of transactions with a clear payment reference and makes it accountable for tax payments. There are countless reasons for using mobile wallets which makes service providers confused and leads them to offer unattractive features in the wallet a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The researchers looked at payment methods before and after demonetization to see if they changed and the results revealed that retailers can benefit if they primarily use digital payment methods post demonetization. Most retailers accept payments through various apps (Manickam, Vinayagamoorthi, Gopalakrishnan, Sudha, & Mathiraj, 2022). Gani and Adeoti (2011) used a pre-tested, standardized questionnaire on electronic payment system adoption to collect primary data, and a multistage sampling technique and the probit model was used for the analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The researchers looked at payment methods before and after demonetization to see if they changed and the results revealed that retailers can benefit if they primarily use digital payment methods post demonetization. Most retailers accept payments through various apps (Manickam, Vinayagamoorthi, Gopalakrishnan, Sudha, & Mathiraj, 2022). Gani and Adeoti (2011) used a pre-tested, standardized questionnaire on electronic payment system adoption to collect primary data, and a multistage sampling technique and the probit model was used for the analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings revealed that platform application, application service, and service strategy complementarities positively impact brand equity and customer loyalty. Manickam et al [123] investigated India's mobile wallet usage trend. According to the results, customers tend to use mobile wallet brands such as Google Pay and Paytm.…”
Section: Customer Engagementmentioning
confidence: 99%
“…It offers a range of services, including mobile recharges, bill payments and online shopping. In addition to its digital wallet, Paytm also offers a payments bank, which allows users to open a savings account and earn interest on their deposits [22].…”
mentioning
confidence: 99%